A case of reversible upper brachial plexopathy following CRT-P implantation - Mathew, Dolly; Lakshman, S. G. Shyam (International Journal of Research in Medical Sciences, 2018)
Brachial plexus injury is a challenging field of hand and upper extremity surgery. Presently available microsurgical techniques and functional gains are rewarding in upper plexus injuries. Cardiac electronic devices implantation rate is the required to manage long-term complications. Cardiac resynchronization therapy (CRT) implantation is a commoner procedure done for severe ischaemic and non ischaemic cardiomyopathy. A 65-year-old male patient underwent CRT device implantation via utilizing his left subclavian vein with a classical incision over the delto pectoral groove, with right ventricular lead on the inter ventricular septum and left ventricular lead into the posterolateral branch of coronary sinus with RA threshold, impedance and amplitude (P) of 1V and 690ohm and 7.8mv respectively. CRT with adjacent nerve structure is carefully selected for vein puncture to minimize the risk of Brachial plexus injury, i.e. pacing lead induces nerve injury. Peripheral nerve injuries are sparsely reported due to procedural as well as indwelling trans venous pacing leads and isolated posterior cord involvement is a rarer presentation hence is reported.